Control of fissures generated by the retraction in rigid pavements, applying synthetic fibers of recycled polypropylene. - Torres, V. (2020)
The retraction affects the setting process and the useful life of the concrete with the appearance of fissures; in last year's studies and methods have been generated to mitigate and control it with the use of different products and applications. The development of road infrastructure with the use of concrete as a rolling folder, requires methods to guarantee the durability and reduce the effects of the efforts incorporated by the use, climatic conditions, support base and restrictions of movement of the structure. To evaluate the effects of recycled synthetic polypropylene fibers in plastic retraction tests (ASTM C 1579), 3 mix designs were prepared with different ratios 58 gr., 116 gr., and 176 gr. of recycled and virgin synthetic fibers; the most significant and positive result to reduce fissures without affecting the resistance of concrete by bending and compression, was 0.50 mm without addition fibers, 0.10 mm and 0.15 mm with 176 gr. of virgin and recycled synthetic fibers. Finally, it can be concluded that adding a ratio of 4 kg per m3 allows good workability, in addition, the costs of the fibers are not representative compared to the high costs for future repairs.